(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2014)
Many economic entities working in multiple industrial fields suffer fromlow techniques in using modern administrative means in their works. The mostused tool in measuring required procedures is to adopt and use quality costs. inspite of complications and bronchial of operations in construction projects, Theresearcher was able to find a structure to quality costs according to traditionclassification (prevention, Appraisal, failure) which enables the calculation ofthese costs and then analyze results and setting standards which can beimplemented in evaluating strategic performance for targeted project. and theforge research in theoretical fly to quality and costs concerning it inconstruction section , as well as strategically performance an balancedscorecard excrete method for evaluation strategically performance , and sidepractical take care the researchers content cost of quality for the researchsampling project and suggestion measurement for strategy performanceevaluation a project with expression effect measures and analyzing cost ofquality on measures balanced scorecard and correct action betterment onproject performance by way of measures cost of quality standard.